2016
DOI: 10.1007/s12311-016-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Pure Cerebellar Ataxia with Homozygous Mutations in the PNPLA6 Gene

Abstract: Autosomal-recessive cerebellar ataxias (ARCA) are clinically and genetically heterogeneous conditions primarily affecting the cerebellum. Mutations in the PNPLA6 gene have been identified as the cause of hereditary spastic paraplegia and complex forms of ataxia associated with retinal and endocrine manifestations in a field where the genotype-phenotype correlations are rapidly expanding. We identified two cousins from a consanguineous family belonging to a large Zoroastrian (Parsi) family residing in Mumbai, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
1
14
0
2
Order By: Relevance
“…11 However, it was not before 2014 that mutations in PNPLA6 were also appreciated as a cause of predominant cerebellar ataxia, 12,13 and it has now been shown that PNPLA6 mutations can even cause pure cerebellar ataxia. 14 In light of these observations of patients with predominant or pure cerebellar disease, the terms “SPG7” and “SPG39” reflect the historical meaning at best — and appear to be misnomers for these patients and phenotypes. The fatty acid 2-hydroxylase gene ( FA2H ) is even part of multiple classification systems.…”
Section: Discovering the Phenotypic And Genetic Spectrum From The Extmentioning
confidence: 99%
“…11 However, it was not before 2014 that mutations in PNPLA6 were also appreciated as a cause of predominant cerebellar ataxia, 12,13 and it has now been shown that PNPLA6 mutations can even cause pure cerebellar ataxia. 14 In light of these observations of patients with predominant or pure cerebellar disease, the terms “SPG7” and “SPG39” reflect the historical meaning at best — and appear to be misnomers for these patients and phenotypes. The fatty acid 2-hydroxylase gene ( FA2H ) is even part of multiple classification systems.…”
Section: Discovering the Phenotypic And Genetic Spectrum From The Extmentioning
confidence: 99%
“…A homozygous mutation in SLC30A9 , which is involved in intracellular zinc homeostasis, was found in a consanguineous Bedouin family with neurological deterioration progressing into severe intellectual disability, profound ataxia, camptocormia, and oculomotor apraxia [ 109 ]. For the first time ever, a report linked PNPLA6 mutations with pure SCA without chorioretinal dystrophy or hypogonadotropic hypogonadism, constituting another example of phenotype expansion [ 110 ]. The next finding is an example of how dominant and recessive mutations in the same gene can lead to completely different phenotypes.…”
Section: Introduction: Advances In the Field Of Rare Diseases Reachedmentioning
confidence: 99%
“…Autosomal recessive cerebellar ataxias (ARCAs) are a clinically and genetically heterogeneous group of neurodegenerative disorders often associated with additional non-cerebellar features [ 1 ]. Particular phenotypes can be found within this group, such as Gordon Holmes (GHS) and Boucher-Neuhäuser syndromes (BNS), in which ARCAs appeared associated with hypogonadotropic hypogonadism (HH) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%